The Payoff Time: A Flexible Framework to Help Clinicians Decide When Patients With Comorbid Disease are not Likely to Benefit From Practice Guidelines - Braithwaite, R. Scott (2009)
BACKGROUND: Practice guidelines rarely consider comorbid illness, and resulting overuse of health services may increase costs without conferring benefit. OBJECTIVE: To individualize a framework for inferring when patients with comorbid illness are not likely to benefit from colorectal cancer screening guidelines. METHODS: We modified the “payoff time” framework (the minimum time until a guideline’s cumulative benefits exceed its cumulative harms) to increase its applicability to a wide range of primary care patients. We show how it may inform colorectal (CR) cancer screening decisions for 3 typical patients in general practice for whom CR screening would be recommended by current guidelines: (1) 60-year-old man with diabetes, congestive heart failure, lung disease, stroke, and substantial frailty; (2) 60-year-old woman with diabetes and obesity, without other comorbidity or frailty; and (3) 50-year-old woman with inflammatory bowel disease. RESULTS: For patient 1, the payoff time for CR screening (minimum time until benefits exceed harms) is 7.3 years, and for patient 2, the payoff time for CR screening is 5.4 years. Evidence is insufficient to estimate the payoff time for patient 3. Because patient 1’s estimated life expectancy is 3.7 years (less than his payoff time), he is unlikely to benefit from CR screening. Because patient 2’s estimated life expectancy exceeds 10 years (greater than her payoff time), she may benefit from CR screening. Because evidence is insufficient to estimate the payoff time for patient 3, the payoff time framework does not inform decision making. CONCLUSION: The payoff time framework may identify patients for whom particular clinical guidelines are unlikely to confer benefit, and has the potential to decrease unnecessary health care.